Conspiracy beliefs predict perceptions of procedural justice - Svenja B. Frenzel; Lotte Pummerer; Sonja Utz; Kai Sassenberg (Scientific Reports)
Abstract During the COVID-19 pandemic, people believing in political COVID-19 conspiracies likely perceived that the government executed power unfairly (i.e., low procedural justice), which might have contributed to the questioning of the government’s legitimacy. This study examines the relationship between conspiracy beliefs and perceived procedural justice regarding COVID-19 policies during the peak and decay of the pandemic (May/June 2022–September 2023). Additionally, we considered the moderating role of economic and health threat. We tested our hypotheses using data from a five-wave study (N = 4939, quota-based). Latent growth curve analysis revealed a negative relationship between conspiracy beliefs (at Time 1) and the starting value of procedural justice (i.e., intercept). Furthermore, conspiracy beliefs were also negatively related to the change of procedural justice over time (i.e., slope): the lower people’s conspiracy beliefs at Time 1, the steeper their increase in procedural justice over time. Health threat weakened the relationship between conspiracy beliefs and the intercept of procedural justice, implying that people with stronger conspiracy beliefs reported lower resentment against COVID-19 policies the more they perceived health threat. Results show the effects of conspiracy beliefs on procedural justice throughout and potentially also beyond the pandemic, while also pointing to important moderators.